Immobilizing Chitosan-Stabilized Palladium Nanoclusters on Titanium Dioxide and Their Catalytic Hydrogenation Properties - Adlim Adlim (Jurnal Matematika & Sains, 2006)
Four methods of immobilization of palladium nanoparticles stabilized by chitosan on the surface of titanium have been conducted. The immobilization techniques were denoted with catalysts symbols of [Pd0-chi-TiO2], [Pd0-chi]-TiO2, [Pd0-chi]-TiO2 - cross and Pd0-[chi-TiO2]. Pd0[chi-TiO2] that was prepared by wet impregnation of palladium ions on the surface of titanium-coated chitosan and palladium ions were reduced by refluxing in methanol, produced palladium nano particles catalyst with high catalytic activities compared with those prepared with other methods. The catalytic activity for conversion of nitrobenzene to aniline at 30 oC and 1 atm followed the trend of Pd0-[chi-TiO2] > [Pd0-chi-TiO2] > [Pd0-chi]-TiO2 > [Pd0-chi]-TiO2 - cross. Most of the palladium metal particles in Pd0-[chi-TiO2] were exposed and dispersed with average size of 7.3 nm, while without chitosan, the particles were larger, aggregated and had of low catalytic activity.